Pengaruh Total Quality Management dan Operasi Integrasi Rantai Pasok terhadap Kinerja Operasi: Survei pada Umkm Bordir di Sentra Bordir Kawalu Kota Tasikmalaya - Dede Risti Romadoni, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine the effect of Total Quality Management and Supply Chain Integration on Operational Performance (Survey on MSMEs Bordir Kawalu Tasikmalaya). The method used in this study is the causal method, with a research sample of 50 respondents who are owners Bordir SMEs located in the Kawalu Tasikmalaya. The analytical tool used in this study is multiple regression. The results show that simultaneously Total Quality Management and Supply Chain Integration have a significant effect on the Operational Performance of MSMEs Bordir Kawalu Tasikmalaya. Partially Total Quality Management has a positive and significant effect on the Operational Performance of MSMEs Bordir Kawalu Tasikmalaya. Partially, Supply Chain Integration has a positive and significant effect on the Operational Performance of MSMEs Bordir Kawalu Tasikmalaya.